Endovascular treatment of calcific lesions of the common femoral artery using atherectomy device associated with scoring balloon angioplasty in diabetic patients with high "major amputation" risk. (June 2022) - Morosetti, Daniele; Chiocchi, Marcello; Argirò, Renato; Salimei, Fabio; Nezzo, Marco; Vidali, Sofia; Gasparrini, Fulvio; Meloni, Marco; Uccioli, Luigi; Gandini, Roberto
Objectives: To investigate the outcomes of patients with calcific lesions in the common femoral artery undergoing endovascular procedures with atherectomy device and scoring balloon angioplasty combined with treatment of steno-occlusive disease of the remaining arterial districts of the lower limb. Methods: Between January 2015 and December 2018, 11 diabetic patients at high risk for "major amputation", with calcific lesions of the common femoral artery and ischemic ulcers requiring endovascular treatment were retrospectively evaluated. Technical success was defined as revascularization of the common femoral artery with a residual stenosis lower than 30%. Primary endpoints were an immediate increase of perilesional transcutaneous oxygen pressure (TCPO2 ) > 40 mmHg, ulcerative lesions improvement up to healing or skin flaps re-epithelialization after minor amputation, limb rescue with rejected major amputation, and resolution of rest pain if present. Results: The success rate of the revascularization procedures was 100%. No patient underwent surgical conversion. One case of peri-operative bleeding at the brachial access site was observed. There were no cases of arterial dissection or undesired distal embolization. The average baseline value of perilesional TCPO2 was 21.8 ± 9.2 mmHg. The mean TCPO2 value was 57.4 ± 7.2 mmHg three days after the procedure ( P < 0.05 ), and 51.2 ± 9.8 mmHg 15 days after ( P < 0.05 ). Minor amputations were performed in five patients with advanced ulcerative lesions. No major amputations were performed in the follow-up period. At 14 months follow-up, one patient developed new occlusion of the CFA for extension from the external iliac artery and underwent a new endovascular procedure. We observed an overall primary patency rate of 91% and a primary assisted patency rate of 100% in our 18-month follow-up. Conclusions: Endovascular approach for severely calcified atherosclerotic lesions of the common femoral artery seems to represent a valid therapeutic option associated with promising results in terms of clinical outcome and low complication rates.